Si Ceria AR: An Augmented Reality-Based Learning Media to Enhance Scientific Concept Understanding and Student Engagement - I Wayan Riski Ananda Putra; I Wayan Widiana; I Nyoman Laba Jayanta (Journal of Education Technology, 2025)
This study aims to design and develop Si Ceria, an interactive Augmented Reality (AR)-based learning media to enhance fifth-grade students’ understanding of science concepts and their learning engagement. The innovation responds to the low levels of student achievement and engagement, attributed to the lack of effective and interactive learning media. Data revealed that students’ science concept mastery in the IPAS subject remains low at 71.75%, and learning engagement is also weak, with 33.41% of students indicating they “never” feel engaged during lessons. Si Ceria was developed to support metacognitive learning by incorporating features that help students monitor and evaluate their learning goals. The media combines 3D illustrations, videos, and textual information to deepen conceptual understanding. The development followed the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed Si Ceria has a very high level of validity, with expert ratings of 0.93 (media), 0.95 (content), and 0.96 (design). It was also rated highly practical by students, with 92.8% expressing satisfaction with its usability and visual appeal. Effectiveness testing indicated significant improvements in both conceptual understanding and learning engagement. Therefore, Si Ceria demonstrates strong potential as an innovative and independent learning tool for elementary science education.